A sustainable and effective potassium hydroxide pretreatment of wheat straw for the production of fermentable sugars. (September 2018) - Xie, Xuejin; Feng, Xiaoyan; Chi, Shanshan; Zhang, Yuedong; Yu, Guang; Liu, Chao; Li, Zhenqiu; Li, Bin; Peng, Hui
Abstract: The development of sustainable and effective pretreatment technology is of critical importance for the conversion of lignocelluloses into bioethanol. In this work, KOH pretreatment of wheat straw with the supplement of anthraquinone (AQ) and sodium lignosulfonate (SLS) was investigated under the relatively mild conditions. The effectiveness of KOH pretreatment was evaluated by enzymatic saccharification. It was found that after the KOH pretreatment with 15% KOH, 0.1% AQ and 2% SLS at 120 °C for 40 min, the final total sugar yields (glucose + xylose + soluble xylan) could reach up to 80%, which was 16% higher as compared to the KOH pretreatment without addition of AQ and SLS under the same conditions. In addition, the spent liquor could be reused twice to maintain a relatively good effectiveness of pretreatment, and it could be used to produce fertilizer due to the high content of potassium. Highlights: KOH pretreatment of wheat straw with the supplement of AQ and SLS was investigated. Wheat straw pretreated by KOH + AQ + SLS had a higher enzymatic digestibility. Spent liquor could be reused twice to get a relatively high final total sugar yields. Spent liquor could be used to produce fertilizer due to the high content of K.